Predictive Analysis using Data Mining Techniques for Heart Disease Diagnosis - Joshi, Siddharth; Sasanapuri, Ashish; Anand, Shreyash; Nandi, Saurav; Nemade, Varsha (International Journal of Engineering and Technology, 2018)
Due to technological advancements in the field of computer science and data warehousing techniques. The healthcare industry ranging from small clinics to large hospital campuses use Content management system which has made the storage and accessing of data a faster option. But these large amounts of data generated are regrettably not mined and the data remains unexploited. Through this research we aim to demonstrate the use of Data Mining algorithm by using python programming language in order to create a desktop-based application which will cater to our aim. This Paper will analyze the performance by comparing the metrics of data analysis like accuracy, precision and recall in order introducing our software solution which tries to be more accurate than the work previously done on Cleveland, VA Hungarian data sets taken from UCI repository [1].Â Â